KOMUNIA POD DWIEMA POSTACIAMI W USTAWODAWSTWIE SYNODALNYM POLSKI PRZEDROZBIOROWEJ - Gręźlikowski, Janusz (Prawo Kanoniczne, 2004)
In the midst of numerous of controversy concerning the Eucharist in the history of Church, the way of taking the Holy Communion by the faithful comes to the lading place. It refers especially to the question of taking the Communion under two forms. For almost thirteen centuries, in Western Church, the usual and common practice of administering the Holy Com munion to the faithful was the Communion in form of bread and wine. On the turn of XII-th and XIII-th century, by means of custom, practice of Communion under one form - bread - became accepted and it has constituted the common rule for almost seven centuries, until The Il-nd Vatican Council, which decided to restore Communion under two forms within the limited range, and this was legitimized by Canonical Law Code from year 1983. Introduction of Communion on the form of bread was justified from one side by theological - practical reasons, but from the other side it constituted breach with primeval tradition of the Church, and first of all with example of Jesus Christ Himself from the Last Supper. This second moment became, on the beginning of XV-th century, a substantial element of considerations and polemics concerning the Communion, starting the movement for reclaim of Communion in two forms for the secular faithful. This movement appeared and developed it self in wide trend of Hussitism, and later it reappear with much stronger force in time of protestant reformation. Facing demands to introduce the Communion in two forms, the Church had to define its point of view and discipline in this question. It was basically expressed in resolutions of councils, decisions of popes and the Apostolic See. The movement demanding introduction of Communion under two forms had also wide repercussion in Polish synodal legislation, which had the goal to enforce common law that refer to a way of taking the Holy Communion. Synodal legislators, based on the law, determined common law principles, which should be observed and followed within the range of administering the Holy Communion. Controversial question of Communion under two forms was not a subject of interest of too many provincial or diocesan synods. It resulted from the fact, that not in every dioceses of Poland in those times, idea of Communion under two forms was as strong, thus requiring to be regulated by the law. Such resolutions were passed by these bishops, whose dioceses were exposed in bigger degree on Hussite influences first, and protestant influences later (it applies to the following dioceses: chełmska, wrocławska, włocławska and chełmińska). Resolutions of synods of these dioceses were essentially justified, definitive, unequivocal and calling to observe specific way of administering the Communion under form of bread.